The Role of Citizenship Education in Shaping Awareness of Democracy and Political Participation in the Digital Era - Afriadi, Bambang; Fitri, Fitri (International Journal of Business, Law, and Education, 2024)
Civic Education (PKn/ Pendidikan Kewarganegaraan) has a crucial role in shaping citizens' awareness and political participation, which is essential for the sustainability of democracy. This research highlights the function of PKn as a conveyor of civic and cultural values, as well as the importance of integrating educational institutions in the teaching system to form democratic future citizens. In addition, the adaptation of PKn to the challenges of globalization and value pluralism is the main focus, including the development of character and morals in accordance with the demands of the times. In the technological era, the aspect of digital citizenship is also a concern, with curriculum evaluations aimed at improving understanding and reducing negative behaviours such as cyberbullying. This research emphasizes that PKn includes not only political and legal aspects but also environmental sustainability and social inclusivity values so as to be able to form citizens who actively participate and be responsible in a democratic society.